2013
DOI: 10.1590/s2317-17822013.05000013
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss in children with HIV/AIDS

Abstract: There were hearing alterations in children with HIV/AIDS analyzed in this study. Discreet hearing losses were the most occurring. We verified statistically significant associations with the use of antiretroviral therapy and otitis. Therefore, we point out the importance of auditory monitoring and intervention as soon as possible, thus favoring adequate development in language and decreasing possible difficulties in learning and social inclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 22 publications
0
16
1
4
Order By: Relevance
“…Other studies have reported a higher prevalence of hearing loss among children living with HIV than our estimates [14,17], potentially because the participants in our study were generally healthier, for instance with a low proportion of patients with WHO Stage III/IV. Furthermore, the BCOE is a tertiary health center with more resources than most health centers in Malawi, including equipment for testing hearing (e.g.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Other studies have reported a higher prevalence of hearing loss among children living with HIV than our estimates [14,17], potentially because the participants in our study were generally healthier, for instance with a low proportion of patients with WHO Stage III/IV. Furthermore, the BCOE is a tertiary health center with more resources than most health centers in Malawi, including equipment for testing hearing (e.g.…”
Section: Discussioncontrasting
confidence: 58%
“…While the World Health Organization (WHO) recommends 25dB or greater as the criteria for hearing loss [27], studies commissioned through the WHO have used 20dB as the cutoff [26], and 20dB is widely considered among audiologists as the cutoff for normal hearing. Furthermore, several studies of hearing loss in HIV-infected children have even used 15dB as the cutoff [13,1617]. Therefore, comparison of prevalence among studies can be difficult when different cutoffs are used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reviews or included an ineligible group of HIV participants such as people with HIV and MDRTB), were not in English ( n = 1) or the full text could not be retrieved ( n = 2) . Two further eligible studies were identified through screening references of eligible papers . Finally, 21 eligible articles were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the eligible studies are summarised in Table . Eleven studies focused on children, nine on adults and one on people of all ages.…”
Section: Resultsmentioning
confidence: 99%